INFLUENCE OF MEDICINAL PLANTS AND VITAMIN E ON PRODUCTIVE PERFORMANCE AND SOME PHYSIOLOGICAL PARAMETERS OF BROILER CHICKENS UNDER HEAT STRESS - Galawezh Kh. Qader,; Ihsan T.Tayeb, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate the influence of adding dietary three medicinal plants and vitamin E on productive performance, serum physiological parameters, immunity and antioxidant status of broiler chickens under heat stress (34 - 38) C° for 35 days. A total of 600 Ross one day old broiler chicks were distributed randomly into eight treatments with five replicates 15 birds per each replicate as follows: T1: broiler were fed standard ration (negative control); T2: 50 mg vitamin E /kg ration (positive control); T3: 5g Dill  powder /kg ration; T4: 10g Dill  powder /kg ration; T5: 5g Adiantum powder /kg ration; T6: 10g Adiantum powder /kg ration; T7: 5g Crataegus powder /kg ration and T8: 10g Crataegus powder /kg ration. Live body weight, feed intake, feed conversion ratio and mortality rate were measured at weekly intervals. There was a significant effect of medicinal plants on live body weight at 35 day. However, non-significant difference was noticed on feed intake, significant differences on feed conversion ratio, mortality and livability%. Regarding male chickens, T3 treatment had significantly higher carcass yield as well as each of T3 male and T4 female had higher dressing percentage. Furthermore, higher production index was found in T4 while, high value of economic figure was shown in T5 as well as significant effect on serum thyroid hormone T3,T4, corticosterone hormone and enhanced total antioxidant capacity and stable malondialdehyde all helped to reduce oxidative stress as well as boost antibody titers of ND and IBD compared with T1. It can be concluded that the supplementation of medicinal plants to broiler´s diet had a beneficial effect on most of broiler performance, improving immunity, resistance characteristics and oxidative stress particularly in T4 (Dill10g/kg) under heat stress.